1975
DOI: 10.1104/pp.56.6.776
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Variation in a Polypeptide Subunit of the Major Storage Protein of the Bean, Phaseolus vulgaris L.

Abstract: Electrophoretic analysis of the major seed protein, GI globulin, from four strains of Phaseolus vulgaris L. revealed a three-banded pattern for two strains having a high methionine content (BBL 240 and PI 302,542). The other two strains (PI 207,227 and P1 229,815) known to have a lower seed methionine content, had a two-banded subunit pattern for the GI globulin. Analytical ultracentrifugation confirmed that globulin from the two-banded strains underwent pHdependent reversible dissociation similar to that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0
4

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 13 publications
4
42
0
4
Order By: Relevance
“…There is some evidence, discussed below, which indicates gene duplication of ccM loci and suggests that ccM..subunit genes may be closely linked. Little information exists on the genetics of the seed storage protein subunits from any legume, other than the work of Romero et al (1975) and Hall et al (1977) on heritable variation in a subunit of a major storage protein of Phaseolus vulgaris and the study of Pisum sativum by Thomson and Schroeder (1978). These latter authors have described five genetic systems (LA-LE) determining the structure of Pisum legumin.…”
Section: Dxscussiomentioning
confidence: 99%
“…There is some evidence, discussed below, which indicates gene duplication of ccM loci and suggests that ccM..subunit genes may be closely linked. Little information exists on the genetics of the seed storage protein subunits from any legume, other than the work of Romero et al (1975) and Hall et al (1977) on heritable variation in a subunit of a major storage protein of Phaseolus vulgaris and the study of Pisum sativum by Thomson and Schroeder (1978). These latter authors have described five genetic systems (LA-LE) determining the structure of Pisum legumin.…”
Section: Dxscussiomentioning
confidence: 99%
“…The molecular weights of the bands obtained in this study correlates with those reported by other researchers. However the method of extraction and characterization of phaseolin can lead to different results obtained by different laboratories (Derbyshire et al,1976).SDS-PAGE analysis of phaseolin has been utilized worldwide as an effective tool in analyzing genetic variability, evolutionary relationships and correlation between molecular weight of the band and genotype among bean populations (Brown et al, 1981b;Mcleester et al, 1973;Romero et al, 1975;Gepts, 1998;Singh, 2001;Rodiňo et al, 2001b).We have also observed that SDS-PAGE analysis was useful in tracking the origins of bean genotypes that have been dispersed into various regions because PAGE analyses revealed any changes in genetic variability during the cultivation process. These changes in the Phaseolin locus (Phs) have been shown in Mesoamerican genotypes rather than Andean genotypes (Gepts, 1993;Kami et al, 1995;Chacon et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…4) show that the subunits are translated individually, as the SDS treatment used will not break covalent bonds. Genetic analysis of subunit patterns from different strains of Phaseolus vulgaris has shown heritable variation of the large subunit of GI independent of the other subunits (17). Taken together, the evidence from the in vitro studies and from genetic analysis makes it almost certain that the GI subunits are under control of separate genes.…”
mentioning
confidence: 99%
“…In previous papers we have described the isolation (15) and characterization (22,23) of Gl globulin. In an accompanying article (17) we describe the inheritance of the largest of the three component polypeptide subunits of GI (15). Developing seeds (12-18 mm long) were used.…”
mentioning
confidence: 99%